MAHASISWA BERCADAR DAN GERAKAN SOSIAL (KAJIAN TENTANG PERSPEKTIF DAN PARTISIPASI MAHASISWA BERCADAR TERHADAP GERAKAN SOSIAL UNIVERSITAS NEGERI MAKASSAR) - Arisnawawi Arisnawawi; Ashari Ismail (PREDESTINATION: Journal of Society and Culture, 2021)
Veiled students are a representation of the teachings of Islam. This religion has several commands or recommendations. Among them help people who are oppressed or wronged. This religious suggestion has a substantial correlation with the aims of the social movement of the UNM student demonstrations. Namely to help people who are oppressed or oppressed. Seeing the harmony between religious advice and the goals of the social demonstration movement, in reality it is rare or even never seen that UNM-veiled students are present in a series of UNM demonstration social movements. This study aims to find out how the perspective of UNM veiled students towards the social movement of UNM student demonstrations and how the participation of UNM veiled students in social movements in general. This research uses a qualitative approach. Location and research informants are at Makassar State University, which are spread over various faculties. Determination of informants is done by purposive sampling involving 20 individuals as informants. The data collection technique was done by observing, interviewing and documenting. Based on the research results, it can be concluded that the perspective of UNM-veiled students towards the social movement of demonstrations at UNM consists of a positive perspective and a negative perspective. The form of participation of UNM veiled students in carrying out social movements is divided into two forms. Namely participation in physical or tangible form and participation in physical or intangible form.